Measurement of escape time of concentrated DNA molecules in front of a nanogap. (22nd December 2020) - Azuma, Naoki; Fukuzawa, Kenji; Itoh, Shintaro
Abstract: In this study, we proposed a method to measure the escape time of DNA molecules trapped in front of a nanogap by concentrating DNA molecules in front of a nanogap and observing the escape process upon their entry. We measured the escape time for λ DNA molecules entering a 25 nm deep nanogap in the semi-dilute unentangled regime to verify the validity of our method. Our obtained escape time was the same order of the relaxation time of the DNA molecule, represented by the Rouse model.